Antimicrobial Activity of Silver Nanoparticles against Clinical Biofilms from Patients with and without Dental Caries - Espinosa Cristobal, Leon Francisco (2021)
Dental caries is an infectious oral disease originated by the presence of different microorganisms from well-defined biofilms. Many treatments for dental caries have been demonstrated to be successful protocols; however, incidence and prevalence remain still high. Although silver nanoparticles (AgNPs) have shown excellent antimicrobial properties, even against different oral bacteria, there is no available scientific information that has evaluated the antimicrobial activity of AgNPs against oral biofilms from subjects with active dental caries. The objective of this research was to evaluate the inhibitory effect of AgNPs in dental biofilms from subjects with and without dental caries. Two sizes of AgNPs were prepared and characterized. Dental plaque samples were collected from 30 subjects with dental caries and 30 subjects with no dental caries. Microbiological analysis was determined by the minimum inhibitory concentration (MIC) of nanoparticles, and the presence and distribution of microbial strains were identified by polymerase chain reaction (PCR) assay. AgNPs had significant antimicrobial effects against all samples of dental plaque; however, the physical properties of AgNPs, as well as specific sociodemographic and clinical conditions from patients, were also associated with bacterial growth inhibition of Ag particles (p < 0:05). PCR confirmed the presence of oral bacteria associated with dental caries, such as S. mutans and S. sobrinus strains, principally. The AgNPs exhibited great potential to be used as an antimicrobial therapy for the control and prevention of dental caries.